THE EFFECT OF VISUAL MEDIA ON SOCIAL STUDIES LEARNING IN SECONDARY SCHOOL - Dini Amalia; Sri Hapsari (Sosio-Didaktika: Social Science Education Journal, 2018)
This study aims to determine differences in social studies achievement in students who use instructional media visuals that do not use. The study was conducted in Yasmine School with a sample size of 40 students. The study used an experimental method, namely by providing pre-test and post-test. Visual learning media can facilitate understanding and strengthen memory, and cultivate students' interest and can provide the relationship between the content of the subject matter with the real world. The use of visual learning media, hopefully not boring learning social studies only look at the text, but with the visualization of the material presented by the teacher, the learning more interesting and challenging.